Screening of Efficient Rhizobium and Vam Fungal Isolates at Varying Levels of N and P Fertilizers - Vasishth, A.; Kaushal, R.; Kaushal, A.N. (Indian Journal of Agroforestry, 2020)
The study was conducted to find out the impact of Rhizobium and VAM fungi at varying levels of N and P fertilizers applications on growth of Acacia catechu raised in polythene bags under quasi-sterilized conditions in glasshouse. Seven authenticated Rhizobium isolates (locally isolated and authenticated) at four levels of N (0, 20,40,60 kg ha-1 and four VAM species culture (Glomus mosseae, Gigaspora gilmorei, Glomus fasciculatum and indigenous VAM consortium) at four P levels (0,30,40,50 kg ha-1) were taken for the studies. Application of N had significant positive effect on total biomass production up to 40 kg ha-1. Among the various levels of N, 40 kg ha-1 was found superior to other levels in enhancing the various plant parameters. Amongst all the isolates inoculation with ACDeli-I produced significantly higher biomass (7.66g plant-1) at 40 kg N ha-1 and lowest (4.23 9 plant-1) was produced by uninoculated control plants receiving non N-fertilizers. The same combination of Rhizobium and N fertilizers was also found to be the most effective in accumulating the highest amount (163.2 mg plant-1) of total N, whereas, uninoculated plants in absence of N could accumulate only 59.2 mg N plant-1. The mycorrhizal colonization, nutrient uptake and plant biomass production differed significantly due to inoculation with various VAM fungi and phosphorus levels. Among the different fungi tested G. gilmorei was found to be the most efficient in increasing these traits in Acacia catechu. The highest (2.7 g plant-1) plant biomass was recorded in plants inoculated with G.gilmorei at 40 kg P ha-l, which was 17 percent more than that of respective control.